Endoscopic sinus surgery for pediatric patients: Prognostic factors related to revision surgery. (6th June 2019) - Wu, Pei‐Wen; Huang, Chien‐Chia; Yang, Shih‐Wei; Huang, Yenlin; Huang, Chi‐Che; Chang, Po‐Hung; Lee, Yun‐Shien; Lee, Ta‐Jen
Abstract : Objectives: In the past two decades, endoscopic sinus surgery (ESS) has been performed frequently in children with medically recalcitrant chronic rhinosinusitis (CRS). However, surgical success rates vary according to age. The causes of failure and prognostic factors for revision ESS remain unclear. The aims of the present study were to evaluate prognostic factors related to revision surgery after ESS, and to determine the most optimal timing for surgery in the pediatric population. Methods: This was a retrospective review in a tertiary medical center. Children who underwent ESS for CRS between 2004 and 2017 were enrolled. Demographics, sinonasal examination findings, previous operation history, laboratory data, comorbidities, and computed tomography (CT) results were collected from medical records. Prognostic factors for revision surgery were analyzed. Results: A total of 188 pediatric patients were enrolled in this study. Twenty‐four patients (12.8%) required revision surgery. Multivariate logistic regression analysis identified patients with nasal allergy (OR = 6.258; P = .010) and higher Lund‐Mackay score on preoperative sinus CT (OR = 1.658; P = .043) had worse outcomes, while older age was a positive prognostic factor (OR = 0.702; P = .018). A cut‐off point of 15.68 years of age and mean Lund‐Mackay score of 10.5 showed the best predictive power for revision surgery. Conclusion: Because ESS is performed with increasing frequency in children, knowledge of prognostic factors for revision surgery is important. In this study, patients with younger age, nasal allergy, and higher Lund‐Mackay score on preoperative sinus CT had worse outcomes. Level of Evidence: 4 Laryngoscope, 130:1051–1055, 2020